PENCEGAHAN TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA BANTUAN SOSIAL DALAM PENANGANAN COVID-19 (Studi Kasus Putusan Nomor: 29/Pid.Sus-TPK/2021/PN.Jkt.Pst) - Idham Chalid (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2023)
Corruption that occurs in the procurement of goods and services (PBJ) is included in the category of extraordinary crimes, not only can harm state finances but also violates the law, social and economic rights of the wider community. A more comprehensive handling of the various problems of criminal acts of corruption in social assistance PBJ is needed in handling Covid-19. This is the background for the authors to conduct research with a normative legal research approach. Conduct analysis related to the implementation of PBJ in relation to laws and regulations as well as the opinions of legal experts. This is very important, in order to be able to describe the various causes of criminal acts of corruption and efforts to prevent them. In the author's note regarding the factors causing the criminal act of corruption in PBJ social assistance in handling Covid-19 as in the case of Decision Number: 29/Pid.Sus-Tpk/2021/Pn.Jkt.Pst, there are two (2) important things: subjective factors and objective. Subjective factors, related to weak personal integrity, because of the urge to fulfill the need for "self-actualization" so that you always exist as state officials and politicians who succeed by violating the law. Objective factors, related to the PBJ implementation system that has not run well, PBJ that is not open and transparent, PBJ implementation procedures that are not in accordance with the rules, internal supervision of APIP which is still weak and the influence of political relations in PBJ. Of course, efforts to prevent criminal acts of corruption are needed which are more optimal so that criminal acts of corruption do not happen again. Maximizing the increase in personal integrity and anti-corruption culture in the implementation of PBJ and improving the PBJ implementation system in preventing criminal acts of corruption by maximizing the role of related parties in the PBJ system. Apart from that, the maximum role of the Corruption Eradication Commission and the PK National Team is also needed in supporting the improvement of the PBJ implementation system which is better and cleaner from collusion, corruption and nepotism (KKN).